2014 IEEE International Ultrasonics Symposium 2014
DOI: 10.1109/ultsym.2014.0656
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dissipated power distribution on BAW Resonators' behavior

Abstract: By taking the spatial distribution of the dissipated power into account the modeling of Bulk Acoustic Wave Resonators at higher power levels could be improved. The simulation results have been verified by measurements of vectorial scattering parameters during high power loads and by measurements of the temperature increase due to the self-heating by infrared thermography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Extension of the 1D model by an additional resistance allows also to take the dielectric losses in the dielectric layers and the resistive losses in the electrodes into account [7]. By an additional parallel resistance also the lateral leaking waves depending on the resonator area can be modeled [8]. The 1D model can then be used to optimize the amount of the acoustic wave confined within the piezoelectric active and not active layers, the reflection of the longitudinal and shear waves by the Bragg mirror and the electric losses by changing the thicknesses of the different layers within a specified range.…”
Section: B Appropriate 1d Modelingmentioning
confidence: 99%
“…Extension of the 1D model by an additional resistance allows also to take the dielectric losses in the dielectric layers and the resistive losses in the electrodes into account [7]. By an additional parallel resistance also the lateral leaking waves depending on the resonator area can be modeled [8]. The 1D model can then be used to optimize the amount of the acoustic wave confined within the piezoelectric active and not active layers, the reflection of the longitudinal and shear waves by the Bragg mirror and the electric losses by changing the thicknesses of the different layers within a specified range.…”
Section: B Appropriate 1d Modelingmentioning
confidence: 99%
“…[10][11][12] A shift of the transfer function to lower frequencies for increasing power levels was reported. [13][14][15][16][17] The research of [18][19][20] indicated that the absorbed power of the resonators had a noticeable left-shift when power increased. And in Refs.…”
Section: Introductionmentioning
confidence: 99%